Exploitation of tumor antigens and construction of immune subtype classifier for mRNA vaccine development in bladder cancer - Zhang, Xin; Zhang, Yanlong; Zhao, Li; Wang, Jiayu; Li, Jiaxing; Wang, Xi; Zhang, Min; Hu, Xiaopeng (Frontiers in Immunology, 2022)
Background: Bladder cancer (BLCA) has high mortality and recurrence despite multimodal therapies. In this study, we aim to identify potential tumor antigens for mRNA vaccines and cancer subtypes suitable for immunotherapy. Methods: Gene expression profiles, mutation data, methylation data, and corresponding clinical information were obtained from the Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO), and ArrayExpress databases. Immunohistochemical staining of microarrays was performed to assess protein expression levels of IGF2BP2 and MMP9. Differential gene analysis, survival analysis, correlation analysis, consensus clustering analysis, and immune cell infiltration analysis were conducted using R software. Finally, the R package “immcluster” was used based on Combat and (eXtreme Gradient Boosting) XGBoost algorithms to predict immune clusters of BLCA samples. Results: Two over-expressed, amplified, and mutated tumor antigens, IGF2BP2 and MMP9, were found to be associated with clinical outcomes and the abundance of antigen-presenting cells (APCs). Subsequently, three immune subtypes, including immune activation (BIS1), immune depletion (BIS2), and immune inhibition (BIS3) subtypes, were defined in the BLCA cohort. Tumors in subtypes BIS1 and BIS2 were more malignant with immune infiltration phenotypes and exhibited a poor prognosis compared to BIS3. We identified five antigens that were differentially expressed between the three immune subtypes. Functional enrichment analysis of the genes related to immune subtypes suggested that they are enriched in many immune-associated processes. Finally, the “immcluster” package was applied to the dataset, which has been shown to accurately predict the immune subtypes of BLCA samples in many cohorts. Conclusions: IGF2BP2 and MMP9 are potential antigens for developing mRNA vaccines against BLCA. These results suggest that immunotherapy targeting these two antigens would be suitable for patients falling under the BIS2 subtype. R package “immcluster” can assist in screening suitable BLCA patients for anti-tumor therapy.